Evolution of global heat transfer coefficient on PCM energy storage cycles. (October 2017) - Esteves, Luís Pedro; Magalhães, Ana; Ferreira, Victor; Pinho, Carlos
Abstract: Using a simple experimental layout, some results on the evolution of global heat transfer coefficient for two phase change materials (PCM), during fusion and solidification processes, were determined. To do this, a system using commercially available thermal oil as the heat transfer carrier was used and the phase change material being tested operated in a fusion and solidification cycle. The heat transfer oil transferred heat to the phase change material during the fusion step and carried heat away from the phase change material during the solidification step. The influence of the mass flow rate of the heat transfer fluid, as well as of its temperature, in the evolution of the overall heat transfer coefficient from the thermal oil to the PCM during its fusion and in the opposite direction during the PCM solidification, for a given experimental set-up, was studied. One of the tested phase change materials was a salt while the other was a paraffin.